PENGARUH DIVIDEND PER SHARE (DPS), NET PROFIT MARGIN (NPM) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Perusahaan Industri Manufaktur yang tercatat di Bursa Efek Indonesia Periode 2012-2015 - Abdurrahman Abdurrahman; Muhammad Agus Salim; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACKThe purpose of this research is to know Dividend per Share (DPS), NetProfit Margin (NPM) and Return on Equity (ROE) on Stock Price. Population inthis research is all Manufacturing Industry Company which listed in IndonesiaStock Exchange period 2012-2015. Technique of sampling in this research usingpurposive sampling of 31 corporations. Analytical techniques in this study usingmultiple linear regression.The results showed that partially Dividend per Share (DPS) and Net ProfitMargin (NPM) have a positive and significant effect on stock prices. Return onEquity (ROE) has a positive and insignificant effect on stock prices. Whilesimultaneously Dividend per Share, Net Profit Margin and Return on Equityberpruh against Stock Price. The result of Adjusted R2 shows that Dividend perShare, Net Profit Margin and Return on Equity contribution amounted to 43.5%against Stock Price.Keywords: Dividend per Share (DPS), Net Profit Margin (NPM) and Return onEquity (ROE) on Stock Price.